HUBUNGAN WORK-LIFE BALANCE DAN LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN KERJA PERAWAT DI RSUD DR. R. SOEDJATI KABUPATEN GROBOGAN - Nurul Widia Wijayanto; Suroto Suroto; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2020)
Job satisfaction is important for the nurses and hospital. If the job satisfaction does not meet the needs of the workers, it will affect the nurses and hospitals. Moreover, there are many factors which encourage job satisfaction. One of these factors is work-life balance and non-physical environment. Therefore, the job satisfaction is important to prevent the absence and the not optimal work of nurses. The aim of this study to determine the relationship of work-life balance and non-physical work environment to nurses job satisfaction at the Regional General Hospital of Grobogan Recency,  Dr. R. Soedjati. This study is a quantitative study by using cross sectional approach. The subjects of this study are the nurses at the gladiolus and lavender wards in Dr. R. Soedjati hospital. There are 40 respondents as total sampling which are tested by using chi square test. The result of this study shows that there is a relationship between work-life balance (p value = 0.001; α = 0.05) and non-physical environment (p value = 0.003; α = 0.05) on the job satisfaction of nurses in Dr. R. Soedjati hospital. It can be concluded that the nurses in Dr. R. Soedjati hospital have a good job satisfaction. Furthermore, Dr. R. Soedjati can conduct outbond family or other recreational activities which invites the family of each nurse. Moreover, the work environment can maximize the performance of nurses to the patients.